Ecological Health Index (EHI) assessment in the Monte-Espinal transition of southwestern Buenos Aires province (Semiárida, 2025)
Drylands are essential for human development in various regions around the world. The Southwestern region of Buenos Aires Province is a semi-arid area affected by significant landscape transformations. This study evaluated the ecological sustainability of livestock farms in the southwest of Buenos Aires Province. The main objective was to adapt the Ecological Health Index (EHI) to local conditions and apply it to assess the ecological sustainability of livestock operations with different management histories. Eight plots were selected, each with distinct land-use histories plowing, burning, and no recent intervention under either adaptive or conventional management. A matrix of indicators, tailored to local conditions, was used. Three 10-meter transects were established at each site, spaced 40 meters apart. Along each transect, five 0.50 m x 0.50 m quadrats were set, within which all indicators were surveyed. The indicator “biological soil crust presence” was included due to its importance in nutrient cycling and water retention. Results showed that sites under adaptive management with no recent intervention had high EHI scores (47 and 39). In contrast, recently plowed or burned sites had lower index values (31 and 39), although some improvement was observed over time since disturbance. In conclusion, the EHI proved to be an effective, low-cost, and easy-to-apply tool for monitoring the ecological health of grasslands in semi-arid zones. Sites under adaptive management demonstrated greater resilience and ecological stability. Implementing this index may guide sustainable management practices, promoting a balance between livestock production and the provision of ecosystem services.
Keywords: livestock; adaptative management; woody vegetation